Sobre a unidade do Fedro de Platão: o movimento psicagógico e a arte retórica - Câmara, Anita Guimarães (2018)
The main objective of this work is to answer the problem of unity in Plato's dialogue, Phaedrus. The justification for this investigation is given by the controversy generated by the various readings made throughout the centuries of this Platonic dialogue. It is intended that, in establishing a unity of the dialogue, a better understanding of the topics addressed (such as myth, rhetoric, soul, dialectic, memory, among others) is possible. In seeking to solve this problem, one aspect that was privileged was a dramatic change and the literary resources of the text. In particular, the character of Phaedrus plays a key role in explaining the unity of dialogue. I propose that the appearance of fragmentation of the dialogue is due to Socrates’ attempt to conduct Phaedrus’ soul (psichagogy), throughout the text. This conduction sought to promote, in the Socratic interlocutor, a better understanding of both erôs and rhetoric. Now, rhetoric is a kind of psychagogy through discourses, and this Socratic conduction of Phaedrus is nothing more than the dramatic act of a true rhetorical art that will be developed in theory in the presente dialogue. The rhetoric in the Phaedrus, therefore, can attain a status of genuine technê for philosophical and pedagogical purposes. This philosophical rhetoric is not, however, a dialectic with another name (as some interpreters have suggested), since it presupposes, in addition to the dialectic, the knowledge of the existing types of souls and the appropriateness of discoureses to each type. The Phaedrus, therefore, is a dialogue that has precisely this appearance because Socrates acts as a philosophical rhetorician and, knowing his friend, he was able to adjust the right speech to the right moment to convince him of the erros and problems of sophistry rhetoric